1994
DOI: 10.1111/j.1467-8624.1994.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Achievement Evaluation: Motivational Implications of Self-Other Differences

Abstract: In order to explore the development of self-evaluative biases, children at 3 age levels (5-6, 7-8, 9-10) evaluated themselves or another child when given social or temporal comparison feedback. Evaluative biases were indicated by higher evaluations for the self than another, especially after failure. Children at different ages were not differentially responsive to temporal vs. social comparison information. However, evaluative bias in response to the type of evaluation differed by age; there was greater bias f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 17 publications
7
44
0
Order By: Relevance
“…In a recent review of the relationship between selffocused attention and negative affect, Mor and Winquist (2002) found that the relationship between rumination and depression was stronger for adults than adolescents. Mor and Winquist suggested this result may be obtained because with age adolescents are less likely to inflate their self-evaluations (Ruble, Eisenberg, & Higgins, 1994), and at the same time they also develop more complex self-schemas (Harter, 1999). Supporting such an assertion, our results suggest that with age the interrelationships between response styles and personality variables become increasingly consolidated and predictable.…”
Section: Discussionsupporting
confidence: 74%
“…In a recent review of the relationship between selffocused attention and negative affect, Mor and Winquist (2002) found that the relationship between rumination and depression was stronger for adults than adolescents. Mor and Winquist suggested this result may be obtained because with age adolescents are less likely to inflate their self-evaluations (Ruble, Eisenberg, & Higgins, 1994), and at the same time they also develop more complex self-schemas (Harter, 1999). Supporting such an assertion, our results suggest that with age the interrelationships between response styles and personality variables become increasingly consolidated and predictable.…”
Section: Discussionsupporting
confidence: 74%
“…Some students will feel they have successfully managed the academic environment if they simply passed a course. The more confidence students have in their own ability, the less they will rely on social comparisons, and the more likely they will achieve independent judgments about their competence (Ruble, 1994;Ruble and Flett, 1988). We have, therefore, separated the construct of academic adjustment (students' internal sense of successful management of the academic environment) from student or institutional-based assessments of individual competence in developing the model for this study.…”
Section: Academic Engagement As An Antecedent Of Academic and Social mentioning
confidence: 97%
“…4. Males have been more likely to enhance their concepts of performance than females (Marsh, Parker, & Barnes, 1985;Marsh et al, 1988;Meece & Courtney, 1992;Ruble, Eisenberg, & Higgins, 1994;Skaalvik & Rankin, 1994;Widaman, Macmillan, Hemsley, Little, & Balow, 1992).…”
mentioning
confidence: 94%